Merancang Sistem Informasi dan Pemasaran Produk UMKM Berbasis Web di Dinas Koperasi Sumut - Br Berutu, Elimiana; Syah, Rahmad (INCODING: Journal of Informatics and Computer Science Engineering, 2024)
MSME actors at the North Sumatra Cooperative Office often experience difficulties in their business. The difficulty that arises in this business is the difficulty of MSMEs/SMEs in marketing their products and finding suitable buyers. This research aims to design and build a web-based marketing information system for MSME actors under the auspices of the North Sumatra Cooperative Office to overcome the limitations of market reach and access to technology. The system uses PHP, MySQL, and XAMPP with the SDLC approach of the waterfall model. The K-medoids clustering method was applied to group MSME data, resulting in a quality cluster with a Davies-Bouldin Index (DBI) value of 0.368812. The grouping results showed that 314 MSME actors deserved a 30% reward, 540 received a 20% reward, and 231 received a 10% reward. This system helps expand marketing reach, make it easier for customers to find products, and increase the competitiveness of MSMEs. This research supports the digital transformation of MSMEs and can be replicated to encourage sustainable economic growth.